Alternating Sword Controller in First-Person Action Game using Fuzzy Logic for Adaptive Enemy - Azra, Arby Azyumardi; Harisa, Ardiawan Bagus (Bina Nusantara University, 2024)
Virtual Reality (VR) has become widespread in the gaming industry, but the high cost of VR devices makes it difficult for gamers to own one. This research provides a solution by creating a new First-Person Action game that has Motion Controller using the gyroscope sensor on smartphones. A game with adaptive difficulty is necessary, as playing a game that is too easy or difficult can lead to frustration and boredom. This research applies the Fuzzy method to implement the adaptivity of the enemy to the player. The Fuzzy system will model the player's ability based on their performance in a level and produce an impact on the enemy in the next level. We produced a simple VR game on a smartphone with a Fuzzy system that automatically adapts the difficulty by using â€œResistanceâ€ as the enemyâ€™s new life. As a result, 90.5% of the 14 respondents that faced the difficulties in each of the levels are being adjusted by the game. Even though the experiences of each respondent are different, most respondents can intuitively play the game without asking for help.